2009
DOI: 10.1590/s0100-40422009000500022
|View full text |Cite
|
Sign up to set email alerts
|

On-line preconcentration system using a microcolumn packed with Alizarin Red S-modified alumina for zinc determination by flame atomic absorption spectrometry

Abstract: A simple and sensitive on-line flow injection system for determination of zinc with FAAS has been described. The method is based on the separation and preconcentration of zinc on a microcolumn of immobilized Alizarin Red S on alumina. The adsorbed analyte is then eluted with 250 µL of nitric acid (1 mol L-1) and is transported to flame atomic absorption spectrometer for quantification. The effect of pH, sample and eluent flow rates and presence of various cations and anions on the retention of zinc was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Preconcentration methods based on solid-phase extraction are attractive when coupled with the detection instrument and with the use of sorbent and chelating agents. These methods provided limit of detection about 0.2 to 29  μ g L −1 and preconcentration factor about 5 to 144 [2329]. As observed, the adsorbent preconcentration method presented here shows better or similar performance when compared with the works previously published in terms of limits of detection and sample consumption.…”
Section: Resultssupporting
confidence: 66%
“…Preconcentration methods based on solid-phase extraction are attractive when coupled with the detection instrument and with the use of sorbent and chelating agents. These methods provided limit of detection about 0.2 to 29  μ g L −1 and preconcentration factor about 5 to 144 [2329]. As observed, the adsorbent preconcentration method presented here shows better or similar performance when compared with the works previously published in terms of limits of detection and sample consumption.…”
Section: Resultssupporting
confidence: 66%
“…AAS is the most widely used method for the determination of Zn. The detection limit of the direct air-acetylene flame method is 50 µg L -1 (Shabani, Dadfarnia, Moosavinejad, & Ahmadi, 2009).…”
Section: Conventional Detection Techniquesmentioning
confidence: 99%
“…They have reported that Pb and Cd as the most prevalent heavy metals were found in several samples (Thabit, Shokr, Elgeddawy, & El-Naggar, 2020). Preconcentration on a microcolumn of immobilized Alizarin Red S on alumina FAAS 0.2 µg L -1 (Shabani, et al, 2009) Chelating with 5,7-dichlorooxine AAS 0.5 μ L -1 (Tony, et al, 1999) In situ pre-concentration with the dual silica tube atom trap AAS 0.3 μg L -1 (Matusiewicz, et al, 1991) CPE pre-concentration FAAS 0.095 μg L -1 (Jianrong Chen & Teo, 2001)…”
Section: Conventional Detection Techniquesmentioning
confidence: 99%
“…The chelating resins can be used in flow injection system with various detection methods like FAAS, ICP-AES, spectrophotometry, chemiluminescence and ICP-MS etc [26].There are various chelating resins have recently been used such as polyurethane foam [27][28][29][30][31][32][33][34][35], cellulose, silica gel [36][37][38][39][40][41][42], alumina [43][44][45][46][47][48], chitosan [49][50][51], carbon active [52] and polymeric resins like Amberlite etc. Amberlite XAD resins widely used to develop several chelating materials for preconcentration procedures due to its good physical and chemical properties such as porosity, high surface area, durability and purity.…”
Section: Applications Of Chelating Resins Based On Amberlite Xad mentioning
confidence: 99%